Temperature and humidity alert system in oil palm tissue culture laboratory via SMS and email notification: article / Norhaslin Nordin - Nordin, Norhaslin (2010)
Malaysian Palm Oil Board (MPOB) is currently undertaking the latest technology on the establishment of a tissue culture laboratory for production of high yield clone oil palm. The main purpose of the tissue culture laboratory was to produce superior planting material through tissue culture or cloning process. This project is expected to be implemented in monitoring the growth of oil palm seedlings by using appropriate method. Furthermore, the usage of wires needs to be minimize as highly as possible to create a well organized and a systematic laboratory. The application of SHTl 1 sensor on oil palm tissue culture equipped with an alert system is the best solution to overcome the problems that currently occurred in MPOB laboratory. Information such as temperature and humidity can be obtained as the SHT11 sensor is used as the single-chip relative humidity and temperature multi-sensor module. For this purpose, SMS alerts and email notifications are developed by using SMS Gateway and mail server to en£>le the user to monitor the parameter data. Once the normal range of temperature and humidity is exceeded, the user will be triggered via SMS and email. An accomplishment of the system has been carried out by using open source software such as SMS Gateway, Mail Server, Apache, MySQL and PHP. Test has been performed and the results clearly showed the capability and the potential of the alert system itself.